2004
DOI: 10.1002/elps.200405926
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the chiral and achiral related substances of methotrexate by cyclodextrin‐modified micellar electrokinetic chromatography

Abstract: A cyclodextrin-modified micellar electrokinetic chromatographic (CD-MEKC) method for the determination of the most important potential impurities of methotrexate (MTX): 2,4-diamino-6-(hydroxymethyl)pteridine, aminopterine hydrate, 4-[N-(2-amino-4-hydroxy-6-pteridinylmethyl)-N-methylamino] benzoic acid, 4-[N-(2,4-diamino-6-pteridinylmethyl)-N-methylamino] benzoic acid, and the distomer D-MTX is presented. The MEKC separation of these compounds was optimized by applying a step-by-step approach. The addition of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The addition of b-CD to the MEKC system based on SDS was essential for the enantioresolution of methotrexate and for the separation of achiral impurities. The application of this method for the analysis of tablets and injections showed that the major impurity was D-methotrexate [157].…”
Section: Enantiomeric Purity Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of b-CD to the MEKC system based on SDS was essential for the enantioresolution of methotrexate and for the separation of achiral impurities. The application of this method for the analysis of tablets and injections showed that the major impurity was D-methotrexate [157].…”
Section: Enantiomeric Purity Testingmentioning
confidence: 99%
“…Baseline separation was obtained using b-CD in a phosphate [157] buffer pH 4.0. The method was applied to measure cefoperazone enantiomers in pharmaceutical doses.…”
Section: Content Assaysmentioning
confidence: 99%
“…A CD-MEKC method to simultaneously determine the chiral and achiral purity of methotrexate was published by Gotti [77]. The method was validated and proved to be sufficiently robust and sensitive for the analysis of commercially available tablets and injection solutions.…”
Section: Pharmaceutical Applications Of Chiral Ce: Applicationsmentioning
confidence: 99%
“…Impurities of L-methotrexate, an antimetabolite of folic acid, and its chiral and achiral impurities were separated using MEKC with cyclodextrin as additive [107]. The method was validated concerning ICH guidelines and applied to quantify the impurities in tablets and injection formulations.…”
Section: Anticancer Drugsmentioning
confidence: 99%